2007
DOI: 10.1177/0883073807307096
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ghrelin in Weight Gain and Growth in Epileptic Children Using Valproate

Abstract: Ghrelin is a major hormone, regulating the energy balance of the body. Weight gain is a significant side effect of valproic acid, which has not been clearly identified pathogenetically. The aim of this study was to investigate the effect of valproic acid on ghrelin and its potential effects on weight gain and growth. Each patient and control group consisted of 35 children aged 3 to 15 years. Fasting serum glucose, insulin, C-peptide, leptin, ghrelin, insulin-like growth factor-1, and insulin-like growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 23 publications
4
31
1
6
Order By: Relevance
“…This is somewhat in contrast to previous studies, since for instance ghrelin levels were increased in children treated with VPA in prepubertal (but not in pubertal) status. 28,29 Yet, Greco et al, 30 found lower ghrelin levels in pubertal subjects who significantly gained weight during VPA treatment. However, if very young prepubertal children were considered separately, total ghrelin levels were decreased prior to/ independent of a consistent weight gain while on CBZ and VPA.…”
Section: Discussionmentioning
confidence: 95%
“…This is somewhat in contrast to previous studies, since for instance ghrelin levels were increased in children treated with VPA in prepubertal (but not in pubertal) status. 28,29 Yet, Greco et al, 30 found lower ghrelin levels in pubertal subjects who significantly gained weight during VPA treatment. However, if very young prepubertal children were considered separately, total ghrelin levels were decreased prior to/ independent of a consistent weight gain while on CBZ and VPA.…”
Section: Discussionmentioning
confidence: 95%
“…Greco et al [13] noted that serum adiponectin and ghrelin levels were significantly lower in adult patients with VPA-associated obesity than those in controls. Güngör et al [19] conducted a study including 35 patients treated with VPA and 35 volunteers aged 3 to 15 years, which showed that serum ghrelin levels were significantly higher in those treated with VPA than those in controls. In the current study, serum ghrelin levels did not significantly change over time.…”
Section: Discussionmentioning
confidence: 97%
“…Recently ghrelin has been investigated with respect to its potential role in epilepsy. Data from human studies in this area are conflicting, with some studies concluding either increased [15,16] or decreased [17][18][19][20][21][22] plasma levels of ghrelin in epileptic patients. Rodent studies are more consistent, with the majority of studies indicating that ghrelin shows an anticonvulsant action in different models [10,[23][24][25], but its mechanism of action is unknown.…”
Section: Introductionmentioning
confidence: 99%